STRATEGI MEMORI LEKSIKAL DALAM PEMBELAJARAN BIPA PEMULA DI HANOI, VIETNAM - Pitaloka, Hersila Astari (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2025)
Based on a needs analysis of BIPA learning in Hanoi Embassy several findings indicate the need for adjustments in the teaching techniques. Therefore, this article aims to present the implementation of lexical memory strategies in beginner BIPA classes at the Indonesian Embassy in Hanoi. This research is descriptive with a qualitative approach. The data is derived from observations of the BIPA learning process. The sources of data are beginner BIPA learners at the Indonesian Embassy in Hanoi, Vietnam. Data collection techniques used are observation and note-taking during the lessons. The research findings indicate that lexical memory strategies are necessary to enhance the vocabulary of beginner BIPA learners. The steps in this teaching strategy are: (1) determining the learning theme, (2) classifying vocabulary for each session, (3) selecting and using supporting media, and (4) practice, evaluation, and enrichment. This strategy helps learners to expand their vocabulary. However, it is important to note that in second language learning, a needs analysis of the learners is crucial.